Pengelolaan dan Pendampingan dalam Pembuatan Minuman Kunyit Asem Ibu Nurhayati Sebagai UMKM di Desa Takerharjo - Alwian, Bagas (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Management in making tamarind drinks is one of the momentum that we want, apart from that we can get various opportunities to find out about original products or typical drinks that are produced directly from Takerharjo village. The drink, which is produced directly by